2013
DOI: 10.1136/jclinpath-2012-201301
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D: a negative acute phase reactant

Abstract: Serum 25-(OH)D is a negative acute phase reactant, which has implications for acute and chronic inflammatory diseases. Serum 25-(OH)D is an unreliable biomarker of vitamin D status after acute inflammatory insult. Hypovitaminosis D may be the consequence rather than cause of chronic inflammatory diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
212
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(225 citation statements)
references
References 13 publications
8
212
4
1
Order By: Relevance
“…24,30,31 The observation of an acute decline from baseline in serum 25(OH)D drawn 48 hours after surgery has even led to the suggestion that serum 25(OH)D is a negative acute-phase reactant. 32 The current study furthers the skepticism about the therapeutic role for nutritional vitamin D in reducing inflammation by showing no effect of increasing serum 25 (OH)D on epoetin responsiveness or hsCRP levels.…”
Section: Discussionmentioning
confidence: 53%
“…24,30,31 The observation of an acute decline from baseline in serum 25(OH)D drawn 48 hours after surgery has even led to the suggestion that serum 25(OH)D is a negative acute-phase reactant. 32 The current study furthers the skepticism about the therapeutic role for nutritional vitamin D in reducing inflammation by showing no effect of increasing serum 25 (OH)D on epoetin responsiveness or hsCRP levels.…”
Section: Discussionmentioning
confidence: 53%
“…Moreover, despite convincing in vitro findings, there are examples of observational studies finding no associations (6), and clinical trials and reviews have been inconclusive about the role of vitamin D (7,8). These inconsistent findings have led to a discussion on whether hypovitaminosis D is a cause or a consequence of inflammation (9,10). There is also no consensus on the definition of optimal vitamin D status (11).…”
mentioning
confidence: 99%
“…[9] Interestingly, serum 25(OH)D shows an inverse relationship with C-reactive protein, although the significance of this relationship is not completely understood. [12,24] As a cross sectional analysis, this study has several inherent limitations. First, we are unable to assess specific trends in serum 25(OH)D. Therefore, perioperative and long term outcomes associated with specific serum 25(OH) D are not revealed.…”
Section: Discussionmentioning
confidence: 99%
“…[9,12] One study reported 77.7% of hip fracture patients had sub-normal serum 25(OH)D versus 58.6% in normal controls. [17] Furthermore, periprosthetic joint infections (PJI) show a close association with vitamin D deficiency in the arthroplasty population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation